1970
DOI: 10.1104/pp.46.3.367
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Stomatal Behavior and Hormonal Imbalance in flacca, a Wilty Mutant of Tomato

Abstract: The wilty tomato mutant, flacca, and the normal variety, Rheinlands Ruhm, were compared for kinetin-like activity in ontogeny. The mutant wilts easily because its stomata resist closure. This stomatal resistance decreases with age. The occurrence of a root factor which induces stomatal opening was inferred from grafting experiments. It was hypothesized that the excessive stomatal openings in thc mutant may result from excess of kinetin -like activity in the leaf of that plant. In addition, it was suggested tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
27
1

Year Published

1970
1970
2005
2005

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 23 publications
6
27
1
Order By: Relevance
“…This suggestion is further supported by the conspicuous curing of the mutant by application of abscisic acid as found by the present authors (5). The possibility of a causal relationship between a lower amount of abscisic acid compounds and higher cytokinin activity (18) and their interaction on the stomatal mechanism is being studied.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…This suggestion is further supported by the conspicuous curing of the mutant by application of abscisic acid as found by the present authors (5). The possibility of a causal relationship between a lower amount of abscisic acid compounds and higher cytokinin activity (18) and their interaction on the stomatal mechanism is being studied.…”
Section: Discussionsupporting
confidence: 53%
“…This increased activity might contribute to the greater closing ability of the mutant stomata with age, in addition to the decrease of cytokinin activity reported before (18). This suggestion is put forward in view of the data showing that synthetic auxins induce closure of stomata of several plants (1,3,9,19,20) including tomato.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…It is now well established that leaves of water-stressed plants contain more ABA (Wright, 1969;Milborrow and Noddle, 1970;Zeevart, 1971;Most, 1971) and less cytokinins Vaadia, 1965, 1971). Detailed investigations with the wilty mutant of tomato also indicated that wilting of plants was associated with the increase in cytokinin content and decrease in ABA Imber, 1970, 1971;Tal, Imber and Itai, 1970).…”
Section: Discussionmentioning
confidence: 99%